Plasmodium malariae in Chittagong, Bangladesh - Haque, Muhammad Ehsanul; Husain, Muhammad Anwar; Akter, Nasima; Mazed, Muhammad Abdul; Alam, Khan Mashrequl; Sultan, Muhammad Tipu; Dewanjee, Arup Kanti; Ahmed, Muhammad Shaqil; Rahman, Muhammad Arifur; Hossain, Muhammad Zakir (Bangladesh Journal of Medical Microbiology, 2013)
We detected a case of Plasmodium malariae in Chittagong, Bangladesh. The person was an adult male, presented clinically as severe malaria. B lood slide examination by microscopy and pan malarial immunochromatographic test (ICT) revealed the case as Plasmodium malariae infection. The patient presented as severe malaria case for which he was hospitalized and recovered after seven days of quinine treatment. DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16936 Bangladesh J Med Microbiol 2011; 05 (02): 30-31